Institutional Function Regional Finances In Managing Regional Assets In Indonesia - Nurmalawaty Nurmalawaty (NOMOI Law Review, 2020)
Regional autonomy as the beginning of decentralization has the urgency to be implemented for the progress of the State. Regional financial institutions often occur collusion triangles with regional heads so that they do not guarantee the implementation of good regional government because of the management of sub-optimal regional assets. The need for maximizing the functions of regional institutions so that regional assets can be managed for regional progress evenly. The absence of special regulations regarding the management of regional finance is a problem because it still uses state financial laws so that the recommendations that the authors recommend in the form of optimizing regional financial institutions in managing regional assets and the existence of special regulations that regulate in detail the management of regional assets. The method used in this study is a normative juridical legal research method.Keywords: Institutional Function, Regional Finances, Regional Assets